Comparison of Speech Quality and Intelligibility Assessments in University Classrooms - Prodeus, Arkadiy; Didkovska, Maryna; Kukharicheva, Kateryna (International Journal of Architectural Engineering Technology, 2021)
Estimates of speech quality and intelligibility for three university classrooms of small, medium and large sizes are presented. The quality and intelligibility of speech were assessed by objective methods using binaural room impulse responses, measured at 5-6 points of the premises. The measures of speech quality were log-spectral distortion (LSD), bark spectral distortion (BSD) and perceptual evaluation of speech quality (PESQ), and the objective measure of speech intelligibility was the speech transmission index (STI). Among the quality measures considered, only BSD is shown to be highly correlated with STI measures for all three classrooms. In this case, correlation coefficient R varies from minus 0.6 for a small room to minus 0.98 for a large room. The close relationship between PESQ and STI is observed only in the case of a large classroom (R = 0.96-0.99), and the LSD measure was found to be uncorrelated with STI for premises of all sizes. The obtained results can serve as a justification for the use of BSD instead of STI, and vice versa, in the acoustic examination of classrooms of different sizes.